Strategi Guru dalam Menerapkan Sistem Evaluasi Formatif dan Sumatif - Dwi friska salsabiela; Nurul Huda Maulidiyya; Ade Dermawansyah Purba (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze teachers' strategies in implementing formative and summative evaluation systems in the learning process. The method used in this study is a qualitative approach with a literature review. Data collection was conducted through systematic literature searches using scientific databases such as Google Scholar and national journal portals. The sources used were then selected based on their relevance to the research topic, year of publication, and source credibility. The results show that teachers have implemented formative evaluation continuously through quizzes, discussions, and questions and answers to monitor student learning progress. Meanwhile, summative evaluation is conducted through written tests and project assessments to measure the achievement of learning outcomes comprehensively. However, there are still obstacles in the implementation of evaluation, such as time constraints and suboptimal analysis of summative evaluation results. This study concludes that teachers' strategies in evaluating learning are quite effective, but need to be improved, particularly in providing feedback and utilizing evaluation results to improve learning. The limitations of this study lie in the use of library research methods, which only focus on reviewing various literature sources and therefore lack direct empirical data from the field. Therefore, this study recommends that further research be conducted through field work to obtain more in-depth and comprehensive data regarding the implementation of learning evaluation strategies applied by teachers in the learning process.